Nick Hughes: capstone - Hughes, Nick, artist (Colorado State University. Libraries, 2015)
The artist's statement: My name is Nick Hughes and I am an aspiring graphic designer. I am 30 years old and am from Loveland, Colorado. Ever since elementary school, I knew that art was my favorite subject. Not only did I like art class the best, it was also the subject I was most praised for, with reading being a close second. My objective is to turn my life-long passion for art into a sustaining career. My path in life hasn't been the easiest one. I was born to parents with substance abuse problems. At the age of seven my parents got divorced, and my mother's new partner made her addiction problems much worse. When I was ten and my little brother was three, we were taken into protective custody. For the rest of both of our youths my brother and I stayed in a foster home. The reason I bring this up is to illustrate my motivation to succeed. I am not ashamed of my past because it has taught me everything I have needed to know in my art and in my life. It has also taught me what I don't want in my life. My experiences show in my art, and these experiences have driven me to the brink of a Bachelor's degree. I am the first member of my whole extended family to attend a university, let alone graduate from one. I may have been able to achieve these goals in a different upbringing, yet I feel it wouldn't be as rewarding as what I feel from what I have achieved so far. My desired career is one in graphic design, though I have a lot of talent in illustration and painting. Whether for a graphic design firm, or for my own freelance business, I want to incorporate all of my art talent and training into my work. I also aspire to use my experiences, my hard work, and my determination to create professional work and lasting memories for my clients.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design